Efficacy of Learning Activity Package on Academic Achievement and Retention among Biology Students in Federal College of Education, Zaria - SHITTU, Adeniyi Michael; OMONIWA, Oluwatope Olubunmi; MICHAEL, Jonathan Dadiya (Ilorin Journal of Education, 2024)
This study assessed the efficacy of the Learning Activity Package (LAP) on academic achievement and retention among N.C.E. Biology students at the Federal College of Education in Zaria, Kaduna State." The study was designed with two aims and two research questions. A quasi-experimental design was implemented. The population consisted entirely of N.C.E. Biology students from the Federal College of Education in Zaria, Kaduna State. The sample size was based on an entire class of 200 pupils. This research employed the Biology Achievement Test (BAT), which consisted of 25 multiple-choice questions with four alternatives and one right answer. Students completed an achievement exam to collect data, which was then analyzed using statistical methods such as the t-test, standard deviation, and mean analysis. The findings show a substantial difference between students taught biology using the Learning Activity Package and those taught using the lecture technique. It was found that teachers at the Federal College of Education in Zaria, Kaduna State, should enhance their techniques of teaching and studying biology. However, it was advised that biology instructors use learning activity packages at all levels of education in Nigeria.